Effects of troxerutin and selenium supplementation in mitigating cypermethrin-induced behavioral impairments and oxidative stress in mice - Shehzad, Sobia; Tahir, Sajid Khan; Yousaf, Muhammad Shahbaz; Masood, Muhammad Irfan; Anjum, Syed Muhammad Muneeb; Khan, Imad (Archives of Biological Sciences, 2026)
Paper description: Previous studies reported the neuroprotective effects of individual supplementation of troxerutin and selenium in terms of improved behavioral functions and redox status against cypermethrin-induced neurotoxicity in rodents. The co-supplementation effects of troxerutin and selenium have not been reported and are the primary focus of this study. A sub-acute mouse model was employed, administering cypermethrin along with single and combined supplementation of troxerutin and selenium. Single and co-supplementations alleviated behavioral deficits, oxidative stress, and normalized serum biomarkers. Abstract: The current research aimed to investigate the potential effectiveness of single and combined supplementation with troxerutin (Trx) and selenium (Se) against cypermethrin (Cyp)-induced neurotoxicity and oxidative stress in mice. Thirty mice were randomly divided into five groups. The control group received 0.9% normal saline orally; the Cyp group received Cyp (5 mg/kg) orally; the Cyp+Trx group received Trx (150 mg/kg) in combination with Cyp; the Cyp+Se group received Se (25 µg/kg) with Cyp; and the Cyp+Trx+Se group received Trx (150 mg/kg) and Se (25 µg/kg) together with Cyp, all administered orally for 28 days. The individual and combined supplementation of Trx and Se significantly improved motor impairment, memory function, hepatic and renal health markers, and reduced anxiety levels (inside time/time in centar zone) in Cyp-exposed mice. Moreover, all supplementations reduced the Cyp-induced oxidative stress, but the SOD activity was increased in the serum and brain by the supplementation of Trx and Se, respectively. Liver and kidney SOD activities were improved with all the supplementations. Combined supplementation of Trx and Se enhanced brain acetylcholinesterase activity compared to the Cyp group. These findings suggest that both single and combined supplementation with Trx and Se confer neuroprotection against pesticide-induced oxidative and behavioral alterations; however, brain acetylcholinesterase activity and renal health markers were improved only by the combined Trx and Se supplementation.